Islam as the state ideology: exploring from Gramsci’s notion of power, culture and ideology - Wan Norshira Wan Mohd Ghazali (Penerbit Universiti Kebangsaan Malaysia, 2019)
The paper aims at establishing relationships between culture, power, and the state ideology. The reading of Malaysian politics through Gramsci’s conceptual framework provides a tentative interpretation on the state’s exercise of power with popular consent, the structure of power, relation between the state and subaltern groups. Reading through the concept of hegemony, the paper explores the construction and enactment of Islam by the power of the state. It highlights how Islam came to be constructed as the state ideology and how the state establishes and maintains the hegemonic position. On this basis, Islam has been used to produce a specific set of structures in Malaysia to gain national-popular support. The state-society relations will be explored through Gramsci’s notion of civil society to illustrate the possible resistance to the state power. The paper suggests that civil society as a field of contestation in Malaysia. The 14th General Election result has demonstrated that ideology could be contested, hence challenging the state’s domination or coercive power. In conclusion, this paper has demonstrated the previous state’s struggle with civil actors in dominating and maintaining its popular ideology. It could be seen how actors of nonconformist voices in civil society have mobilised themselves into organised groups and institutions to undermine the state hegemony thus assisting the change of the ruling power in the GE14. After 61 years of Independence, Malaysia is finally celebrated the new ruling party.